Nonlinear magnetoelectric effects of multiferroic composites. (1st March 2021) - Hu, Zhi-Ming; Su, Yu; Li, Jackie
Abstract: Magnetoelectric effect is one of the most important features in multiferroic composites which is absent in either ferromagnetic or ferroelectric composites. In this paper, a two-level micromechanics model is developed to study the nonlinear magnetoelectric (ME) effects of multiferroic composites consisting both ferromagnetic (or magneto-strictive) and ferroelectric (or piezoelectric) materials. At the first level, the model involves a thermodynamically based evolution of the product domain from the parent one in ferromagnetic phase which provides the nonlinear response of the system under the external loading. And at the second level, it treats the ferromagnetic and ferroelectric as a two-phase composite, and Eshelby based micromechanics is applied to obtain the overall effective properties of the composite. Then the two-level model is used to study the nonlinear magnetoelectric effects of Terfenol-D/PZT/Terfenol-D laminated system under the applied magnetic field first, and then under the combined mechanical and magnetic field in different directions. To verify the model, the theoretical calculations have been compared with the existing experimental data for both single phase Terfenol-D at the first level and the two-phase Terfenol-D/PZT/Terfenol-D multiferroic composite at the second level. The comparisons between the theory and experiment are in a good agreement.